Material Examination on StatutoryCharacterized Policy Regulations - Annisa, Arini Nur; Riza, Marwati; Wenda Juniar, Mutiah (International Journal of Psychosocial Rehabilitation, 2020)
he concept of policy regulation has similarities with statutory regulations, consequently, there is no clarity about the substance of policy regulations. This study aims to analyze the position of policy regulations that are characterized by laws and regulations and determine the form of the examination of statutorycharacterized policy regulations (beleidsregels). The type of this research is normative juridical. Data collection through library research (Library research). The result shows that the position of policy regulations (beledsregels) which are characterized by laws and regulations are classified as material policy regulations based on the aspect of charge markers / substance based on discretion without delegation authority; and are regulating, and using nomenclature of statutory regulations. The form of testing of regulations characterized by laws and regulations through judicial review can be carried out in accordance with substantial material requests, whereas through legislative review cannot be done based on the concept of policy regulation as an instrument of executive discretion and does not include legislative products. The method of testing policy regulations that are characterized by legislation through executive review is testing by the executive through cancellation by government officials / superiors’ officials issuing policy regulations, namely the minister of home affairs, governor, regent / mayor. Issuance of Decree (SK) in the form of clarification results on the improvement / amendment to the procedures / substance and revocation of material policy regulations, thus, they are not legally binding.